2018
DOI: 10.3389/fpls.2018.01190
|View full text |Cite
|
Sign up to set email alerts
|

Iron and Zinc in the Embryo and Endosperm of Rice (Oryza sativa L.) Seeds in Contrasting 2′-Deoxymugineic Acid/Nicotianamine Scenarios

Abstract: Iron and Zn deficiencies are worldwide nutritional disorders that can be alleviated by increasing the metal concentration of rice (Oryza sativa L.) grains via bio-fortification approaches. The overproduction of the metal chelator nicotianamine (NA) is among the most effective ones, but it is still unclear whether this is due to the enrichment in NA itself and/or the concomitant enrichment in the NA derivative 2′-deoxymugineic acid (DMA). The endosperm is the most commonly consumed portion of the rice grain and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 81 publications
(115 reference statements)
1
39
0
Order By: Relevance
“…Therefore, this technique can provide both quantitative data and spatially revolved imaging of multiple elements. So far, this technique has been applied in analysis of plant dried sample such as seeds (Wang et al ., ; Diaz‐Benito et al ., ), and different organs including stems and leaves (Tian et al ., ). However, there is a limit to apply this technique to map elemental distribution in fresh plant tissues due to element loss and structure destruction during sample preparation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this technique can provide both quantitative data and spatially revolved imaging of multiple elements. So far, this technique has been applied in analysis of plant dried sample such as seeds (Wang et al ., ; Diaz‐Benito et al ., ), and different organs including stems and leaves (Tian et al ., ). However, there is a limit to apply this technique to map elemental distribution in fresh plant tissues due to element loss and structure destruction during sample preparation.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, these observations imply that regulation of NA-PS metabolism is crucial for Fe-homeostasis in graminaceous plants. In line with these speculation, recent studies revealed that different DMA/NA ratio impacted the content of Zn and Fe in embryo and endosperm, and altered the local distribution patterns of Fe in embryo [34], shedding light on the balance between DMA and NA affects Fe-homeostasis.…”
Section: Introductionmentioning
confidence: 62%
“…It is noteworthy that excessive production of NA lead to subsequently increasing of DMA, which may increase Fe content in seed [34]. Consistently, different NA to DMA ratio regulated by NAS and NAAT had different effects on Fe content in grains [34,59]. Therefore, exploring enzymes involved in the synthesis and transport of NA and DMA may provide a theoretical basis to optimize iron bioforti cation in cereals.…”
Section: Zmdmas1 Under Fe De Ciency the Accumulation Of Zmdmas-l2 Zmentioning
confidence: 93%
See 1 more Smart Citation
“…Better results were achieved in the OE OsNAS2 plants with a Fe level-up to 19 μg/g in polished rice (Johnson et al, 2011) in comparison with the Nipponbare wildtype (4.5 μg/g), or in the OsNAS3 and OsNAS2 activation tag plants with 12 and 10 μg/g Fe in milled rice respectively compared to the wildtype (4 μg/g) (Lee et al, 2009b, 2012). A high Fe increase up to 55 μg/g was reported in the endosperm of japonica rice by OE of OsNAS1 and HvNAAT genes (Diaz-Benito et al, 2018). The Fe level is exceptionally high for the starchy endosperm suggesting either Fe contamination or the presence aleurone layer.…”
Section: Biofortification: Agronomic Vs/and Genetic In Rice and Wheatmentioning
confidence: 99%